Pelatihan Jurnalistik Untuk Siswa Kelas XI MA Darussalam Barambai - Ridha Anwari (Jurnal Pengabdian UntukMu NegeRI, 2020)
This service aims to improve students' mental and academic abilities in understanding and practicing journalistic issues, especially writing news articles. The method used in this service is in the form of lectures, discussions, questions and answers, simulations of writing news articles, and evaluating. The target in this service is class XI students in MA Darussalam Barambai consisting of only 1 class. The results of this community service show that class XI students in MA Darussalam Barambai get good grades in the simulation of making articles / news manuscripts. 80% have reached the completeness criteria and passed. 20% is still in the realm of space and needs more practice in writing article scripts.